2021
DOI: 10.1080/23311975.2021.1923355
|View full text |Cite
|
Sign up to set email alerts
|

The role of human brands in consumer attitude formation: Anthropomorphized messages and brand authenticity

Abstract: The purpose of the study attempts to assess consumer reactions by classifying anthropomorphized messages according to the authenticity of a human brand with which they are associated. And also the study to investigate the causal relationship between attributions of human brand and consumer-brand relationships, brand attitudes, and purchase intention. An experimental design was used to test the hypotheses. To examine factors that can help brands achieve marketing goals through the use of human brands, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…This study found that compared with non-anthropomorphic design, the interactive persuasion interface with anthropomorphic design caused users to have more positive attitudes and attracted more users [ 85 , 86 ]. This suggests that the alarm clock and the moon that add human-like features such as eyes and expressions to the interactive persuasion interface may endow the viewer with sensory associations [ 34 ], in turn activating the inanimate object’s life-oriented intention association [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that compared with non-anthropomorphic design, the interactive persuasion interface with anthropomorphic design caused users to have more positive attitudes and attracted more users [ 85 , 86 ]. This suggests that the alarm clock and the moon that add human-like features such as eyes and expressions to the interactive persuasion interface may endow the viewer with sensory associations [ 34 ], in turn activating the inanimate object’s life-oriented intention association [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This concept highlights the attributes exhibited by an influencer and seeks to build a comprehensive perception in the minds of followers/viewers on social media platforms. Social media users often build relationships with influencers that mirror conventional interpersonal relationships, which include emotions, expectations, needs, cognition, motivation, and behavior (Han et al, 2021;Malik et al, 2023).…”
Section: Literature Review Human Brand Theorymentioning
confidence: 99%